Mullerian Adenosarcoma of Uterus with Sarcomatous Overgrowth and Heterologous Component Associated with Stromal Deposit in Omentum: A Case Report and Review of the Literature - Anuradha Sinha; Jyoti Prakash Phukan; Sanjay Sengupta; Paulami Guha (Case Reports in Medicine)
Background. Mullerian adenosarcoma with sarcomatous overgrowth (MASO) is a very rare variant of uterine sarcomas first described by Clement et al. as early as 1974. The presence of heterologous sarcomatous components is associated with aggressive biological behavior. Case Presentation. This is a case report of a 62-year female (P2 + 0) presenting with postmenopausal vaginal bleeding. Her preoperative USG revealed subserosal fibroid with adherent omentum. She underwent abdominal hysterectomy with bilateral oophorectomy. Histopathological diagnosis of resected specimen was Mullerian adenosarcoma with sarcomatous overgrowth and presence of heterologous elements involving body of the uterus. The whole thickness of the myometrium was involved along with the presence of serosal nodules and omental deposits of sarcomatous component. Conclusion. MA is considered as a low-grade malignant tumor, but MASO is a high-grade tumor frequently associated with invasion and metastasis with poor treatment outcome. Because of its rarity, correct identification of these tumors and distinction from other uterine sarcomas are a challenging job and hence its morphological features merits attention.